An empirical investigation of the relationship between the exchange rate and interest yields : a case study of South Africa - Sikwanda, Andrew (Department of Finance and Tax, 2015)
This study analyses the relationship between the Dollar/Rand exchange rate and the interest yields rates in South Africa. It makes use of data available from 1998 through to 2010. Using statistical analysis of regression analysis and co integration, the study found that a positive correlation exists between the dollar/rand exchange rate and interest rate yields.